Comparison of Clinical and Demographic Characteristics and Disability at 6-Months Post Neurologic Onset Among Puerto Rico Guillain-Barré Syndrome Patients with and Without Evidence of Zika Virus Infection. (4th October 2017) - Dirlikov, Emilio; Major, Chelsea; Medina-Lopes, Nicole; Lugo-Robles, Roberta; Matos-Melendez, Desiree; Munoz-Jordan, Jorge L; Garcia-Negron, Myriam; Thomas, Dana; Luciano, Carlos; Sharp, Tyler; Deseda, Carmen
Abstract: Background: Guillain–Barré syndrome (GBS) is a post-infectious autoimmune disorder characterized by progressive weakness due to peripheral nerve damage. In February 2016, Puerto Rico Department of Health and CDC implemented a surveillance system to identify GBS cases during a Zika virus (ZIKV) outbreak. Data were analyzed to describe GBS patients with evidence of ZIKV infection. Methods: Healthcare providers submitted case report forms and GBS patient specimens (i.e., serum, urine, CSF, and saliva) for ZIKV testing. Specimens were tested by RT-PCR; serum and CSF were also tested by IgM ELISA. Patients positive by RT-PCR and/or IgM ELISA were classified as having evidence of ZIKV infection. GBS diagnosis was confirmed and clinical data were collected via chart review after hospital discharge or >28 days post neurologic onset for patients still hospitalized. Telephone interviews collected disability data at 6-months post neurologic onset using the Modified Rankin Score, Overall Disability Sum Score, and Facial Disability Index. Results: Clinical and demographic characteristics of 71 patients with evidence of ZIKV infection were compared with 30 patients without evidence of ZIKV infection. Data on 6-month disability were available for 59 (83%) patients with and 24 (80%) patients without evidence of ZIKV infection. Patients with and without evidence of ZIKV infection did not differ by median age, median illness duration, frequency of previous illness, most neurologic signs and symptoms, medical interventions, clinical outcomes, or most disability at 6 months post neurologic onset. GBS patients with evidence of ZIKV infection were more likely to be female (49% vs. 27%, P = 0.036) and have a previous rash (52% vs. 10%, P < 0.001), facial weakness (59% vs. 27%, P = 0.003), facial paresthesia (18% vs. 0%, P = 0.009), and excessive tearing or dry eyes at 6 months post neurologic onset (51% vs. 25%, P = 0.046). Conclusion: GBS patients with evidence of ZIKV infection were clinically similar to those without evidence of ZIKV infection, but more likely to have facial weakness and paresthesia during acute neurologic illness and report abnormal tear production at 6 months post neurologic onset. Pathophysiologic investigations should examine potential ZIKV autoimmune response preferential effect of cranial nerves among GBS patients. Disclosures: C. Luciano, Sanofi-Genzyme Corporation: Speaker's Bureau, Speaker honorarium. National Institutes of Health (NIH): Grant Investigator, Grant recipient